Current NEXRAD Cannot Reliably Enable Safe Flight Around Heavy Weather. Issue 1 (2nd April 2016) - Knecht, William R.
ABSTRACT: Objective : We wished to assess whether current-generation in-cockpit looping Next-Generation Radar (NEXRAD) can reliably enable safe flight around severe ("heavy") convective weather. Background : Numerous studies suggest that estimating the closest point of approach (CPA) to heavy weather is difficult, and that current in-cockpit NEXRAD may be intrinsically inadequate for the task. Method : To investigate theoretically, we first examined the visual information present in looping NEXRAD. This predicted inherent task difficulty. Next, to investigate empirically, we developed a mathematical model of an "ideal storm, " generated a looping NEXRAD-type part-task simulation, and tested 21 general aviation (GA) pilots to measure effects of weather system depth (19 vs. 40 nm), and the opening and closing of gaps at various closure rates between cells (14, 7, 0, 7, 14 kt). Results : For the values tested, weather system depth had no significant effect on clearance from heavy weather (>40 dBZ reflectivity). However, weather movement greatly degraded safety. Moreover, it did not seem to matter if movement was as slow as 7 kt, nor whether gaps were opening or closing. Any weather movement made an already difficult task more so. Conclusion : Analysis suggests the necessity of adding future-predicted weather plus a range ring. Without these two key elements, judgment of CPA will clearly remain difficult. Training is also necessary to improve performance, but is unlikely to be sufficient.